Emotional Health, Self-Acceptance in Child Victims of Violence and Parental Perception - Faiqah, Syajaratuddur; Annisa, Annisa; Zulaikha, Alodya; Ningsih, Aprilia (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2025)
Background: Children represent the most vulnerable age group to becoming victims of violence, with estimates indicating that one in every two children experiences some form of violence annually. Recent data show an increasing trend in reported cases, reaching 28,845 in 2025, with the highest prevalence occurring among those aged 13–17 years (35%). Such violence results in substantial psychological consequences, including anger, anxiety, depression, shame, self-blame, fear of social interaction, and diminished self-image. Accordingly, this study aims to examine differences in emotional health and self-acceptance among children who have experienced violence and to assess parental perceptions before and after the provision of educational video interventions.Method: The research employed a One-Group Pre-test Post-test design, with the study population consisting of child victims of violence aged over 10 years. Using a total sampling technique, the sample included 62 child respondents and 62 accompanying parents. Comparative data analysis was carried out using the Wilcoxon test to examine differences between the Pre-test and Post-test results.Result: The results of the statistical analyses demonstrated significant improvements across all measured variables, with emotional health showing a marked increase (p = 0.000), as the mean score rose from 29.81 before the intervention to 50.27 afterward. The self-acceptance variable also exhibited a significant change (p = 0.002), increasing from a mean score of 20.45 prior to the intervention to 23.45 following its implementation. Similarly, parental perception improved significantly (p = 0.000), with mean scores increasing from 35.89 to 55.32 after the intervention. Collectively, these findings indicate that the video-based intervention positively influenced the emotional health and self-acceptance of child victims of violence, while also enhancing the perceptions of their accompanying parents, thereby suggesting that video-based educational materials can be effectively integrated into psychosocial support services.